Neutrality Effects on the Phase Structure of the Linear Sigma Model with the Non-standard Symmetry Breaking - Phat, Tran Huu; Long, Nguyen Van; Thu, Nguyen Van (Communications in Physics, 2012)
The neutrality effects on the phase structure of the linear sigma model with the non-standard symmetry breaking term is systematically studied by means of the Cornwall-Jackiw-Tomboulis effective potential. The latter quantity is calculated in the improved Hartree-Fock approximation which preserves the Goldstone theorem and the thermodynamic consistency. Its results that in the region \(μ > m_π\), as a function of the temperature \(T\), the pion condensate undergoes a second order phase transition, as a function of the isospin chemical \(μ\), it undergoes a first order phase transition. In the region \(μ < m_π\), the pion condensation is always a first order phase transition.